Le dolmen du Villard, Lauzet-Ubaye (04) et le contexte funéraire au Néolithique dans les Alpes méridionales Réflexions sur le mobilier et les pratiques funéraires au Campaniforme en Provence - Sauzade, Gérard; Schmitt, Aurore (Préhistoires de la Méditerranée, 2020)
The Villard dolmen is the only preserved megalithic monument of a small group of eight alpine dolmens discovered near Gap and disappeared at the end of the 19th century. Situated at the confluence of the Durance and the Ubaye rivers, it was reported as early as 1894. Research on this tomb as well as its restoration took place from 1980 to 1983. The good conservation of the human bone remains and furniture has favoured the detailed study of the functioning of the burial and the treatment of the remains. Radiocarbon dating has made it possible to identify two periods of use, one in Ancient Bronze and the other in Campaniform. This burial site hosted at least 25 immature and adult individuals of both sexes. The furnishings are specific to the Campaniform. During part of the occupation, the deceased were placed in the centre of the room. A storage area for bones, once the bodies had decomposed, was located at the bedside. At its top, two connected vertebrae of oxen, probably corresponding to an offering, were placed on four stones. To the north, an almost empty space of bones could have been used as a circulation space. In the preserved part of the burial mound to the west, fragments of human bones and some objects of the Middle and Final Bronze were discovered. This study of the Villard dolmen is accompanied by an assessment of funerary practices in Provence during the Campaniform and during the nearby periods, based on a corpus of burials that allows us to evaluate their evolution.